Canonical and civil marriage from the perspective of Western legal dualism. A historical analysis of the issue - Ryguła, Piotr (Prawo Kanoniczne, 2024)
Legal dualism, argued the famous Polish historian Feliks Koneczny (1862-1949), is a feature of Latin civilisation. It refers to the existence of two opposing, but to a certain extent complementary, spheres of legal relations that exist within the framework of man-made law, e.g. ius civilis and ius naturale/iusgentium, private and public law, state law and canon law. The basis of this dualistic perspective in law is a deeper and more primordial understanding of the world, rooted in philosophical and religious values. It is at this level that the perception of the world from the dualistic perspective of the sacred and the profane has been developed. It is also where the dualistic perception of natural law originated: on the one hand, as a transcendent foundation of immutable principles rooted in nature (which are the source of legal norms), and on the other, as a set of norms rooted in human nature and therefore universal. Over time, this dualism has found its institutional reflection. On the one hand, as J. M. Kelly notes, the Catholic Church became associated with an interpretation of ius naturale in the Aristotelian-Thomistic tradition, with an explicit reference to transcendence. On the other hand, the eighteenth-century liberal state, in codifying its law, referred to the idea of an ius naturale based on naturalis ratio, i.e. a human understanding of the world that is natural to man, based on knowledge and interpretation by human reason. In this context, another legal dualism also characteristic of the Western legal tradition - sacrum and profanum - took on a new meaning. It is difficult to imagine that this has not been translated into marriage law as legislated by the Church and the State: each from its own perspective. The Church, which sees marriage as an institution of natural law raised to the dignity of a sacrament, and the State, which sees marriage as an institution of law regulated by human reason, determined by the current state of human knowledge and consciousness.